2014
DOI: 10.1111/wrr.12205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of growth factors and cytokines in wound healing

Abstract: Wound healing is a complex and dynamic biological process that involves the coordinated efforts of multiple cell types and is executed and regulated by numerous growth factors and cytokines. There has been a drive in the past two decades to study the therapeutic effects of various growth factors in the clinical management of non-healing wounds (e.g. pressure ulcers, chronic venous ulcers, diabetic foot ulcers). For this review, we conducted a nonline search of Medline and Pub Medical and critically analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
589
2
37

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(636 citation statements)
references
References 108 publications
(223 reference statements)
8
589
2
37
Order By: Relevance
“…Two different bioactive molecules were selected to create a bioactive coating: (i) chondroitin sulfate (CS), a glycosaminoglycan of the extracellular matrix that participates in the integrity of the arterial wall in normal aortas [9] and exhibits anti-apoptotic properties [10]; and (ii) epidermal growth factor (EGF), a major actor of wound-healing [11] presenting both anti-apoptotic and pro-proliferative properties [12,13]. This choice is based on previous studies that have shown the superiority of the combination of CS and EGF [14].…”
Section: Methodsmentioning
confidence: 99%
“…Two different bioactive molecules were selected to create a bioactive coating: (i) chondroitin sulfate (CS), a glycosaminoglycan of the extracellular matrix that participates in the integrity of the arterial wall in normal aortas [9] and exhibits anti-apoptotic properties [10]; and (ii) epidermal growth factor (EGF), a major actor of wound-healing [11] presenting both anti-apoptotic and pro-proliferative properties [12,13]. This choice is based on previous studies that have shown the superiority of the combination of CS and EGF [14].…”
Section: Methodsmentioning
confidence: 99%
“…Efforts to reduce the problems associated with wound areas have a long history. Now, in conjunction with advances in the field of biotechnology, new treatment models have been developed 1,2 . Platelet rich plasma (PRP) involves a number of biologically active matters, such as thrombocyte granules, catecholamine, serotonin, adenosine triphosphate, albumin, fibrinogen, osteonectin, osteocalcin, calcium, and various coagulation factors, as well as growth factors, such as platelet-derived growth factor (PDGF), transforming growth factor alpha (TGF-α), TGF-β, insulin-like growth factor, fibroblast growth factor (FGF), vascular endothelial growth factor (VEGF), interleukin-1, plateletderived angiogenesis factor, and epidermal growth factor (EGF), which have local effectiveness [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…При этом происходит высвобождение вазоактивных веществ и факторов роста -белков, которые инициируют процессы заживления ран путем привлечения и активации фибробластов, эн дотелиальных клеток, макрофагов и т.д. [1,2,7,8]. В связи с тем что в регуляции регенера торных процессов установлена роль иммун ной системы, некоторые авторы пытаются ускорить регенерацию с помощью цитокинов и стимуляторов иммунитета, особенно мак рофагов.…”
Section: Introductionunclassified